Applied business tools and technologies in tourism and hospitality - Rodolfa, Bernardo B. (Manila : Unlimited Books Library Services & Publishing Inc., 2022)
"This book entitled Applied Business Tools and Technologies in Tourism and Hospitality, First Edition is the updated version of the original Management Information Systems in Tourism and Hospitality Industry book. It identifies common tools, technologies and techniques used in the Tourism and Hospitality industry. It includes an overview of the applications or systems composed of technical processes, methods, software, and hardware that have evolved and streamlined certain functions in the workplace."
Includes references.
English.
Keywords: Tourism -- Technological innovations; Hospitality industry -- Technological innovations